Reliability Improvement Using Sectionalizer with Section Technique Method - liliana liliana; Zulfatri Aini; Hanif Naufal Qasthari (UIN Sultan Syarif Kasim Riau, 2021)
Unreliability in the 20 kV distribution system at PT. PLN (Persero) Rayon Rumbai feeder Rusa is more caused by disturbances that occur. During 2020 this feeder was recorded to experience the highest disturbance of 83 times, causing the system to experience frequent blackouts. This study seeks to identify and improve the reliability of the system in the feeder. The reliability of the system can be calculated and analyzed in more detail with the Section Tehnique method. This method can identify reliability by breaking the system into several sections so that the reliability of each section can be known. The increase in reliability is done by adding a sectionalizer to a system that has low reliability, there are two scenarios that are carried out in placing this sectionalizer correctly to produce better reliability. The results of the calculation of the reliability of each section of the system using the Section Technique method have been obtained, the average value of each reliability index is SAIFI 11.231 (f/customer.yr), SAIDI 30.55 (hr/customer.yr), CAIDI 11.015 (hr/customer interruption). ). The results of this index calculation do not meet the standards of SPLN 68-2 1986 with SAIFI 3.2 (f/customer.yr) and SAIDI 21.9 (hr/customer.yr). The reliability improvement was carried out by implementing sectionilizer on the feeder and the reliability index was obtained with SAIFI values 9.8185 (f/customer.yr), SAIDI 27.5292 (hr/customer.yr) and CAIDI 11.223 (hr/customer interruption) with an increase in SAIFI percentage. by 10.4%, SAIDI 8.8% and CAIDI 0.37%. With the addition of a sectionilizer, it is very helpful in increasing reliability, although it still does not meet the expected standard values.Unreliability in the 20 kV distribution system at PT. PLN (Persero) Rayon Rumbai feeder Rusa is more caused by disturbances that occur. During 2020 this feeder was recorded to experience the highest disturbance of 83 times, causing the system to experience frequent blackouts. This study seeks to identify and improve the reliability of the system in the feeder. The reliability of the system can be calculated and analyzed in more detail with the Section Tehnique method. This method can identify reliability by breaking the system into several sections so that the reliability of each section can be known. The increase in reliability is done by adding a sectionalizer to a system that has low reliability, there are two scenarios that are carried out in placing this sectionalizer correctly to produce better reliability. The results of the calculation of the reliability of each section of the system using the Section Technique method have been obtained, the average value of each reliability index is SAIFI 11.231 (f/customer.yr), SAIDI 30.55 (hr/customer.yr), CAIDI 11.015 (hr/customer interruption). ). The results of this index calculation do not meet the standards of SPLN 68-2 1986 with SAIFI 3.2 (f/customer.yr) and SAIDI 21.9 (hr/customer.yr). The reliability improvement was carried out by implementing sectionilizer on the feeder and the reliability index was obtained with SAIFI values 9.8185 (f/customer.yr), SAIDI 27.5292 (hr/customer.yr) and CAIDI 11.223 (hr/customer interruption) with an increase in SAIFI percentage. by 10.4%, SAIDI 8.8% and CAIDI 0.37%. With the addition of a sectionilizer, it is very helpful in increasing reliability, although it still does not meet the expected standard values.